2018
DOI: 10.1021/jacs.8b10059
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Ullmann Coupling to Bishelicenes by Surface Topochemistry

Abstract: The comparison of the self-assembly 9,9′-bisheptahelicene on the Au(111) surface, studied with scanning tunneling microscopy, with the self-assembly of the same species obtained by on-surface synthesis via Ullmann coupling from 9-bromoheptahelicene reveals a diastereomeric excess for the (M,P)-meso-form of 50%. The stereoselectivity is explained by a topochemical effect, in which the surface-alignment of the starting material and the organometallic intermediate sterically favor the (M,P)-transition state over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Beyond the relatively weak supramolecular (non-covalent) self-assembly, recent developments in on-surface synthesis 1315 pave the way to study chemical reactions between chiral molecules to produce stable chiral products on surfaces. The confinement effect of a 2D surface will kinetically favor either homochiral or heterochiral intermolecular reactions and, as a result, the reactions typically exhibit diastereoselectivity 1618 .…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the relatively weak supramolecular (non-covalent) self-assembly, recent developments in on-surface synthesis 1315 pave the way to study chemical reactions between chiral molecules to produce stable chiral products on surfaces. The confinement effect of a 2D surface will kinetically favor either homochiral or heterochiral intermolecular reactions and, as a result, the reactions typically exhibit diastereoselectivity 1618 .…”
Section: Introductionmentioning
confidence: 99%
“…The chirality is another issue within on‐surface chemistry. Mairena et al. compared the self‐assembled structures of 9,9′‐bisheptahelicene with the same species obtained by on‐surface synthesis via Ullmann coupling, and it indicated that a surface may induce stereoselectivity by topochemistry.…”
Section: Othersmentioning
confidence: 99%
“…Pioneering work from De Schryver and coworkers reported on the conservation of adsorption-induced chirality from self-assembled domains of diacetylene molecules to homochiral polymeric lattices, 20 as recently did Chi and coworkers using alkylated benzenes. 21 Focusing on intrinsic molecular chirality (rather than adsorption-induced), particularly noteworthy is the use of helical aromatic molecules (so-called helicenes) to study the diastereoselective formation of helical dimers [22][23][24] or the transmission from the helical chirality of the molecular precursors to the planar chirality (prochirality) of nanographene adsorbates through a sequence of single-molecule reactions. 25 However, no studies have yet reported e.g.…”
Section: Introductionmentioning
confidence: 99%